The effect of stranded marine debris on the mangrove ecosystem in the coastal area of Liquiça Municipality of Timor-Leste - Santos, Alzira de Jesus dos; Damar, Ario; Hariyadi, Sigid; Fonseca, Abilio da (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
This study aims to determine the types, abundance and composition of the stranded marine debris and its impact on the mangrove ecosystem in Liquiça Municipality, Timor-Leste. Data were collected from 6 September 2024 to 30 October 2024 at three stations using surveys and direct field observations. Analysis was conducted both quantitatively and qualitatively. Seven types of debris were identified : plastic, metal, glass, rubber, fabric, organic and other inorganic waste. Plastic was the most dominant at all stations, Station 1 recorded the highest debris abundance at 1.62 items/m², with plastic waste also dominating by category at Stations 1 and 3 (155 items/m² and 137 items/m²). Station 1 also had the heaviest debris weight at 4,339 g/m² and the largest volume at 235 cm³/m². The findings indicate that stranded marine debris does have a negative impact on the mangrove ecosystem, significant negative correlation between the weight of marine debris and macrozoobenthos. However no correlation between debris and mangrove’s seedlings was found.